ORACLE DIPLOMACY IN PRE-COLONIAL IGBO LAND - Odeke, Francis C.; ONUOHA, Ikechukwu O. (EBSU Journal of Social Sciences and Humanities, 2024)
Oracle Diplomacy is the nurturing of relationships through religious beliefs based on deities or oracles.Oracle diplomacy is not the same as cultural diplomacy but is part of it. Cultural diplomacy extends relations through cultural practices like marriage, festival, masquerade, title taking, et cetera. But in oracle diplomacy, Oracle Priests are the visible diplomats that nurture and sustain relationships with people and groups from within and far away who seek the services of the Priests and their oracles. This study uses the primary and secondary sources of data to prove that Africans had good knowledge of diplomacy with well established means and institutions that encouraged mutual relations and economic growth before the Europeans and Arabs invaded the continent. The study is centred on the Igbo nation of Nigeria where religious beliefs were extensively used in peace building and good inter-group relations. Its methodology is the thematic and analytic approaches of history. From available facts, Igbo people were a deeply religious group; they knew and worshipped a Supreme Being through intermediaries called oracles or deities; and they and their clients believed and revered the messages of the deities as divine and effective. With these developments, the paper discovered that everywhere in pre-colonial Igbo land and other near and far communities, oracles answered both personal and communal needs of adherents, helped the spread of Igbo pre-colonial religion as well as extended their foreign interests. With these advantages, the paper holds the opinion that oracle diplomacy as a natural way of relationship in the early days of the Igbo could be of use to the modern day international community if meticulously incorporated into global affairs, especially the elusive peace and security questions which are paramount to economic drives.